2018
DOI: 10.1038/s41598-018-26946-9
|View full text |Cite|
|
Sign up to set email alerts
|

Quantification of Water Flux in Vesicular Systems

Abstract: Water transport across lipid membranes is fundamental to all forms of life and plays a major role in health and disease. However, not only typical water facilitators like aquaporins facilitate water flux, but also transporters, ion channels or receptors represent potent water pathways. The efforts directed towards a mechanistic understanding of water conductivity determinants in transmembrane proteins, the development of water flow inhibitors, and the creation of biomimetic membranes with incorporated membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
57
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 58 publications
0
57
0
Order By: Relevance
“…S4) where V r ( t ) is the relative volume of the vesicle at time t , P f is the osmotic water permeability coefficient, A / V 0 is the surface area–to–volume ratio of a vesicle, C in and C out are initial solute concentrations inside and outside the vesicle, respectively, and V W is the molar volume of water. We also compared the water permeability coefficients obtained with this procedure with the values determined with a different protocol ( 44 ) that computes permeabilities directly from the time constants and found that both approaches give permeability values that differ by less than 10% (with the second approach producing systematically higher values). The unitary water permeability P w of CNTPs was calculated using the following expression after subtracting the background vesicle permeability where A is the surface area of the CNTP-LUVs, and N is the average number of CNTPs in the vesicle.…”
Section: Methodsmentioning
confidence: 99%
“…S4) where V r ( t ) is the relative volume of the vesicle at time t , P f is the osmotic water permeability coefficient, A / V 0 is the surface area–to–volume ratio of a vesicle, C in and C out are initial solute concentrations inside and outside the vesicle, respectively, and V W is the molar volume of water. We also compared the water permeability coefficients obtained with this procedure with the values determined with a different protocol ( 44 ) that computes permeabilities directly from the time constants and found that both approaches give permeability values that differ by less than 10% (with the second approach producing systematically higher values). The unitary water permeability P w of CNTPs was calculated using the following expression after subtracting the background vesicle permeability where A is the surface area of the CNTP-LUVs, and N is the average number of CNTPs in the vesicle.…”
Section: Methodsmentioning
confidence: 99%
“…As previously described, we monitored the intensity of the scattered light at 90° at a wavelength of 546 nm. 28 The integral water permeability ( P f ) of the LUVs was obtained by fitting eqn (1) to the experimental data: 8 , 31 I ( t ) = a + b [ αV bare ( t ) + (1 – α ) V AQP ( t )] + d [ αV bare ( t ) + (1 – α ) V AQP ( t )] 2 where α in eqn (1) is the fraction of bare vesicles, which did not contain AQP4. V ( t ) depends on P f according to: 8 , 31 where V w , V 0 , A , c in,0 , c out , c Δ , and L are the molar volume of water, vesicle volume at time zero, surface area of the vesicle, the initial osmolyte concentration inside the vesicles, the outer and the incremental osmolyte concentration in the external solution due to sucrose addition, and the Lambert function L ( x )e L ( x ) = x , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The approximate solutions (β) may lead to a large error in P f – more than an order of magnitude in size. 89 Moreover, P f erroneously seems to depend on the osmotic gradient. In contrast, scanning electrochemical microscopy 58 and fluorescence self-quenching experiments (analyzed using a numerical solution) 90 show that P f does not depend on the osmotic gradient.…”
Section: Water Flux Through K + Channelsmentioning
confidence: 99%
“…Eqn (14) has been used to calculate the p f values of several AQPs, 22 , 37 hSGLT1, 36 and KcsA. 91 It may be substituted by the following approximation that ensures acceptable accuracy: 89 …”
Section: Water Flux Through K + Channelsmentioning
confidence: 99%
See 1 more Smart Citation